2012
DOI: 10.1111/j.1365-2044.2011.06983.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of forced‐air warming on the performance of operating theatre laminar flow ventilation*

Abstract: SummaryForced-air warming exhaust may disrupt operating theatre airflows via formation of convection currents, which depends upon differences in exhaust and operating room air temperatures. We investigated whether the floor-to-ceiling temperatures around a draped manikin in a laminar-flow theatre differed when using three types of warming devices: a forced-air warming blanket (Bair Hugger TM ); an over-body conductive blanket (Hot Dog TM ); and an under-body resistive mattress (Inditherm TM ). With forced-air … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 22 publications
0
35
0
1
Order By: Relevance
“…It has been shown that forced-air warming systems can create significant temperature gradients within the operating room that have the potential to disrupt laminar airflow patterns [71] and contaminate the surgical site with floor-level air mobilised by convection currents [72]. However, contesting the notion that these devices disrupt operating room ultra-clean airflow patterns, a recent study using smoke as a visual tracer demonstrated effective laminar airflow in the presence of a working forced-air warming system [73].…”
Section: Forced-air Warming Device Safetymentioning
confidence: 99%
“…It has been shown that forced-air warming systems can create significant temperature gradients within the operating room that have the potential to disrupt laminar airflow patterns [71] and contaminate the surgical site with floor-level air mobilised by convection currents [72]. However, contesting the notion that these devices disrupt operating room ultra-clean airflow patterns, a recent study using smoke as a visual tracer demonstrated effective laminar airflow in the presence of a working forced-air warming system [73].…”
Section: Forced-air Warming Device Safetymentioning
confidence: 99%
“…However, close attention should be paid to avoid burn injury, surgical wound contamination and the effect of hot airflow on surgical sites (Dasari et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…14 The effect of excess heat produced by different warming systems has been analysed and FAW was found to produce the highest amount of excess heat when compared with other warming systems. 56 In this study, pockets of hot air were found above the operating site, which is against the flow of the UCV flow, and these authors have suggested that this indicates a significant disruption to the unidirectional nature of UCV flow. Again, this study could not make any conclusions about whether these changes would be a direct infection risk but they identified that there may be ways to mitigate this potential risk by channelling the warm air out of the UCV flow.…”
Section: Disruption Of Clean Air Through Thermal Eddiesmentioning
confidence: 93%
“…Again, this study could not make any conclusions about whether these changes would be a direct infection risk but they identified that there may be ways to mitigate this potential risk by channelling the warm air out of the UCV flow. 56 Other researchers have studied particle counts over operating sites in UCV flow comparing no warming, FAW, and radiant warming. 59 They found a highly statistically significant increase in the number of particles of all sizes tested in the FAW group compared to other groups (Figure 4).…”
Section: Disruption Of Clean Air Through Thermal Eddiesmentioning
confidence: 99%
See 1 more Smart Citation